Development of instruments for problem-solving, cultural literacy, and conservation attitudes in biology education - Nurlia Nurlia; Nurhayati B; Syamsiah Syamsiah; Hilda Karim (Biosfer: Jurnal Pendidikan Biologi, 2026)
Assessment instruments are essential for evaluating students’ competencies in biology learning, particularly problem-solving skills, cultural literacy, and conservation attitudes. However, validated instruments specifically designed for biosystematics and plant taxonomy learning are still limited. This study aims to develop assessment instruments that can be used to measure students' problem-solving skills, cultural literacy, and conservation attitudes in biosystematics and plant taxonomy learning. The study employed a research and development (R&D) approach by adapting the ADDIE model, focusing on the analyze, design, and develop stages. The instrument development process was carried out through theoretical studies, indicator determination, grid preparation, instrument item formulation, expert validation, limited testing, and validity and reliability analysis. The developed instruments consisted of a problem-solving skills test in the form of essay questions, a cultural literacy questionnaire, and a conservation attitude questionnaire using a Likert scale. Validation was conducted by two experts in Biology Education, assessing content, construct, language, appearance, and instruction aspects. The validation results indicated that all instruments were valid, with average scores of 4.25 for the problem-solving skills test, 4.375 for the cultural literacy questionnaire, and 4.25 for the conservation attitude questionnaire. Reliability analysis showed Cronbach’s alpha values of 0.730, 0.910, and 0.733, respectively, indicating good to very high reliability. These findings demonstrate that the developed instruments are valid and reliable for assessing students’ problem-solving skills, cultural literacy, and conservation attitudes. Future studies are recommended to conduct broader field testing to further examine the effectiveness and generalizability of the developed instruments.